APPLYING THE IMPLEMENTATION OF COOPERATIVE LEARNING TYPE MAKE A MATCH TO ENHANCE THE STUDENT’S COOPERATION AND LEARNING ACHIEVEMENT SPORTS STUDY (Research On Big Ball Game For Students Of X Class Nurse SMKN 4 Lebong) - Rachmad Cahyadi; Johanes Sapri (DIADIK, 2019)
The aim of this research is to enhance student’s cooperation and learning achievement in for Students of X Nurse SMKN 4 Lebong. The research subjects were 22 people students, 11 men and 11 women students. By applying the Implementation of Cooperative Type Make A Match Model. The kind of this research is classroom action research which was conducted in three cycles. Procedure used involves planning, Implementation, observation and reflection. The research instrument that had been used is the test namely the objective test which had been trial the validity and reliability of test and also the observation sheet for observation the learning activity of the students and teacher.To try the significance of student’s cooperation and learning achievement in first to third cycle, it is used t-test, and in first cycle the calculation gained tcount = 2,02. In second cycle the calculation gained ttable = 2,10. And in  third cycle, the calculation gained tcount = 2,30 By comparing the tcount and ttable it is  gained tcount > ttable namely 2,30 > 2,02. Thus, the learning achievement of Sport subject in the first post test at first cycle to third post test in second cycle is significance. So that the learning activity in first post test at first cycle and second post test second cycle is significance also.Based on the result it’s recommended to the teachers in applying the model of Make A Match type according to their owns situation.